Comparison of Post-Operative Recovery Characteristics by Using Isoflurane and Sevoflurane in Adult Patients under General Anesthesia - Fazal, Samsaam; Naeem, Akhtar; Asim, Muhammad; Shah, Abid Ullah; Riaz, Mudssar; Shafique, Hajra; Zafar, Ruqqaya; khan, Afifa Asif; Ferozi, Fatima; Ahmed, Khalil; Bin Lal, Muhammad Zakria (Indus Journal of Bioscience Research, 2025)
Background: Inhaled volatile anesthetics remain the most widely used drug for the maintenance of general anesthesia, because of the ease of administration and predictable intraoperative and recovery characteristics. Over the past years, there have been three gases and thirteen volatile anesthetic agents made available for clinical use. Objective: To determine which agent is safer and causes good post-operative recovery characteristics. Methodology: This comparative cross-sectional study was conducted in four hospitals including 150 patients and divided into 75 males and females each. Sevoflurane and isoflurane were given to 75 each. Both drug groups were supervised closely in the recovery unit and data was collected through a well-constructed performa and analyzed through SPSS version 26th and M.S Excel 2013. Results: Postoperative recovery characteristics of sevoflurane and isoflurane were observed, i.e. tachycardia, bradycardia, hypoxia, hypotension, hypertension, dispend, salivation, suffocation and vomiting. Both groups were closely observed and after a full comparison of postoperative recovery characteristics statistically, it is proved that sevoflurane was showing good results in every characteristic in comparison to isoflurane. Conclusion: The current research study concludes that sevoflurane has good post-operative recovery characteristics in comparison with isoflurane in adult patients having ASA physical status-1. So, sevoflurane should be preferred in patients where better postoperative recovery is needed.